Kadar Yodium Ibu dan Dampaknya terhadap Konsentrasi Yodium ASI: Analisis - Ingrid Siahaan; Joshua Princeman Sinaga (PT Kalbe Farma Tbk., 2025)
Adequate iodine intake during pregnancy and lactation is vital for thyroid hormone synthesis which iscrucial for fetal and neonatal development, especially with exclusive breastfeeding. This review explores the link between maternal iodine levels and breast milk iodine concentration (BMIC), focusing on factors infuencing maternal iodine and its impact on BMIC. This review synthesizes current findings on the determinants of maternal iodine status, including dietary intake, supplementation, and iodine metabolism, and their impact on BMIC underscores the necessity for healthcare providers to monitor and guide iodine intake in pregnant and lactating women. The fndings advocate for targeted public health interventions and the implementation of robust guidelines to ensure adequate iodine nutrition.